Pengaruh Islamic Branding dan Religiusitas Terhadap Minat Masyarakat Muslim dalam Berwakaf Uang - Rianda Hanis; Pertiwi Alifiani (Journal of Finance and Islamic Banking, 2020)
This study aims to look at the influence of islamic branding variables, religiosity variables and attitude variables on the interest of Muslim communities in representing money. This study uses a quantitative approach and Partial Least Squares-Structural Equation Modeling as a data analysis method used to analyze the factors that affect the interest of Muslim communities in the representation of money. Respondents are Muslim communities who have had 141 respondents. The results showed that the Islamic branding variable had a positive and significant effect on attitudes, then the religiosity variable had a positive and significant effect on attitudes.